PENGARUH PEMBERIAN EKSTRAK ETANOLIK DAUN SAMBUNG NYAWA (Gynura procumbens (Lour.) Merr.) TERHADAP KADAR TRIGLISERIDA SERUM PADA TIKUS JANTAN GALUR WISTAR RESISTEN INSULIN DENGAN INDUKSI FRUKTOSA DAN DIET LEMAK TINGGI - , ARINI LAILY WULANSARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Diabetes mellitus (DM) type 2 is metabolic disorder of carbohydrate, fat, and protein which characterized by tissue resistance to the action of insulin. High fat and carbohydrate consumption can improve free fatty acid level in muscles that thus decreasing the sensitivity of insulin receptors. The aim of study was to determine the effect of ethanolic leaf extract of Gynura procumbens (Lour.) Merr. on serum trigliseride levels of insulin resistant rats with fructose and high-fat diet. The study was conducted with a completely randomized design. As many as 26 rats were divided into 6 groups. The control group of normal diet, high fat-fructose diet groups: a negative control with induction of CMC-Na suspension 0.5%, a positive control induction of simvastatin 0.9 mg/Kg BW, and three treatment groups of ethanolic extract induction dose 50, 100 and 200 mg/Kg BW orally. Extract was made by maceration method using 70% ethanol. High-fat fructose-induced rats was given for 65 days, followed by administration of the extract for 15 days. Triglyceride levels were measured by enzimatic methods using reagent TG-FS on days 0, 65 and 80 with 95% confidence level. The result of total flavonoid measurement is 6.87Â±0.02%. The result showed that the ethanolic extract significantly suppressed trygliceride serum in diabetic-rats type 2 resistant insulin. Percent suppression of the elevated serum trygliceride levels in dose of 50, 100, and 200 mg/Kg BW and simvastatin at 43.57Â±9.07%